Monogenic Functions in Conformal Geometry - Eastwood, M.; Ryan, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
Monogenic functions are basic to Clifford analysis. On Euclidean space they are defined as smooth functions with values in the corresponding Clifford algebra satisfying a certain system of first order differential equations, usually referred to as the Dirac equation. There are two equally natural extensions of these equations to a Riemannian spin manifold only one of which is conformally invariant. We present a straightforward exposition.